Transient Horner's syndrome after single shot paravertebral block - Gölboyu,Birzat Emre (2018)
Abstract Background Thoracic paravertebral block can provide analgesia for unilateral chest surgery and is associated with a low complication rate. Horner syndrome also referred to as oculosympathetic paresis, is a classic neurologic constellation of ipsilateral blepharoptosis, pupillary miosis, and facial anhidrosis resulting from disruption of the sympathetic pathway supplying the head, eye, and neck. Case report We present a patient with an ipsilateral transient Horner syndrome after ultrasound guided single shot of 15 mL 0.25% levobupivacaine for thoracic paravertebral block at T5–6 level. Conclusions It should be kept in mind that even a successful ultrasound guided single shot thoracic paravertebral block can be complicated with Horner syndrome due to unpredictable distribution of the local anesthetic.